A Work study on Golden Loaf Inc. - Gayon, Mark Anthony; Libo-on, Salvacion; Noveras, Edward; Pineda, Abigail Concepcion (Diliman, Quezon City College of Engineering, 1993)
Golden Loaf, Inc. is a fast growing company that was begun in June of 1998 by Mr. Raffy Benitez together with his wife. The plant site is a rented one floor building at the back of a market in Cubao. Data showed that the top earner among the products is the Master Pullman, which also constitutes the largest production volume. The plant operates from Sunday to Friday. Saturday is devoted to general cleaning of the plant. The group documented the existing system prevailing within the manufacturing company through meticulous observation and questioning of the appropriate persons. The study consists of three phases : methods study, work measurement and systems and procedures. The study revealed that for the 20 or more products manufactured, a common process is followed with minor modifications (depending on the product). These products are divided into two general classifications : bread and pastry. The plant itself is divided into two general classifications : bread and pastry. The plant itself is divided into these two divisions. When the ingredients arrive at the plant, these are stored in the pre-mix sections, awaiting proper measurement. Everyday, ingredients are weighed and put in separate plastic bags, ready for mixing. The next destination is the dough kneader. An operator pours the ingredients one by one, together with water and mixes for about fifteen minutes, depending on the product to be made. The kneaded dough either goes straight to the roller machine (this kind of dough is called straight dough) or is placed in big plastic drums to undergo fermentation for two hours. These drums are located between the mixers and the rollers. After fermentation, non-straight dough also undergoes rolling at the roller machine. There are three roller machines for the bread division and also three mixers/dough kneaders. An important thing : the dough that completes fermentation first is also the first to be taken to the roller. This operation finished, the operator carries the dough to one of two cutting tables where it is shaped and placed in their respective containers. Dough is allowed to rise for about two hours before being taken to the oven. Baking time depends on the quality of the dough, whether it was allowed to rise for a long time or not. Fully risen dough can be cooked in a high temperature, and thus, baked in just a few minutes while dough that is not fully risen has to be cooked in gradually increasing temperature, thus, a longer cooking time. Baked products are removed from molders and placed on screens before being taken to the gondolas where these are allowed to cool. After two hours these are packaged at the packing table. These processes were recorded using process charts. The methods study conducted by the group revealed several problems that the group hopes to alleviate through the recommendations forwarded. It was noted that the company does not have definite inspection procedures to check the quantity and quality of products. This is only one of the notable problems of the company. Others will be discussed in the body of the study. The working conditions were deemed to be below standard. There were no windows to allow for proper ventilation thus causing excessive heat in the plant especially near the ovens. This may pose a health risk to the oven operators. Added to this is the slippery floors that are also dirty. Needless to say, sanitation is also a problem. The workers are also not provided with seats where they can rest when they are not doing their jobs. Work measurement revealed that there are a lot of idle and ineffective time. The work contained in the production of every product was determined through observations of the workers while at task, timing them and consequently computing the standard time. Allowances for relaxation and personal needs of the workers were taken into consideration. Documentation of the systems and procedures employed by the company was done through flowcharts and organizational charts. Analysis of the forms was done to check the adequacy of the forms used in the operations. The systems and procedures used was analyzed in its relation to the whole structure of the company. How the company performs its everyday operations is documented in the body of the study. The group has concentrated its efforts on improving the facilities of the plant. Several drawings of the innovations proposed such as use of the trolley, are shown inside.
Feasibility study
Keywords: Golden Loaf Incorporation; Bread industry; Systems analysis